Graduate Training and Employment in Brazil - Velloso, Jacques; Balbachevsky, Elizabeth (International Higher Education, 2015)
Since the late 1960s, the Brazilian federal government has directed substantial resources toward the newly created graduate level at the most prestigious Brazilian universities. Direct support for high-level graduate programs provided by CAPES and other Brazilian agencies, bypassing the university bureaucracy, has allowed programs to recruit Ph.D. holders educated abroad as faculty members. Contrary to the experience at the undergraduate level, the government and the academic community have made a decisive effort to assure quality at the graduate level. The Fundação Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES)—the Ministry of Education agency in charge of graduate education—has created a sophisticated peer review evaluation system that successfully connects performance with support at this level. This evaluation, relying on the contribution of acknowledged academic leaders in all areas of knowledge in the country, has enhanced academic legitimacy; program evaluations in each area currently tend to be widely accepted by the academic community. Such programs have become the main or sole sites for the institutionalization of research in the Brazilian higher education system.